Effect Of Tualang Honey Treatment On Human Keloid And Normal Fibroblast And Its Relationship With TGF-Β Expression - Mohamad Shah, Nurul Syazana (2011)
Keloid scar develops on the human skin after trauma, surgery or burn. Keloid grows beyond the boundaries of the wound site and is distinguishable from hypertrophic scar. Due to discomfort caused by keloid growth especially at exposed area, keloid excision might be needed. However, recurrence is common after surgical incision. Tualang honey is a local honey which is found on Tualang tree known as Koompassia excelsa found in Southeast Asia rainforests. Tualang honey is a multifloral honey which is produced by Apis dorsata or Asian rock bees that nested on the Tualang tree.